Arrangement of Kendran Village, Tegallalang District, Gianyar Regency From Study Model Towards Tourism Village - Djaja Bharuna S, Anak Agung Gde; Salain, Ketut Muliawan; Aritama, Anak Agung Ngurah (ASTONJADRO, 2024)
An area/village rearranging model is a series of initiatives to revitalize the village by enhancing strategic and substantial values from regions that still have promise. Kendran Village is one of the villages in Tegelalang District, Gianyar Regency, that has been inhabited by people since the 4th century BC. This settlement was frequently battled for by many kingdoms in Bali throughout the royal period. The natural potential, broadness of rice fields, and presence of two rivers around the settlement give it a distinct topography. Kendran Village is frequently visited by visitors due to the presence of relatively original village structures as well as many interesting relics from the past. Taking into consideration the development and influence of not properly planned tourism development around the Kendran Village area, which has a negative impact on the environment and local cultural heritage, it is deemed necessary to carry out an arrangement as a guiding model for the revitalization of the Kendran Village area. The descriptive qualitative research approach was utilized, depending on theoretical discussion and based on the collection of physical observational data, non-physical interview findings, and references to existing literature. The outcomes, in the form of a structural model for a tourist town, might be oriented at beneficial changes and advancements for the local community's socio-cultural, environmental, and economic situations.